2005
DOI: 10.1002/elps.200406168
|View full text |Cite
|
Sign up to set email alerts
|

A new type of migrating zone boundary in electrophoresis: 1. General description of boundary behavior based on electromigration dispersion velocity profiles

Abstract: Till now two principal types of electrophoretic boundaries have been recognized: a steady-state one showing self-sharpening properties and an unsteady-state one showing electromigration dispersion (EMD). In this contribution, the existence of a third (hybrid) type of electrophoretic boundary is revealed, that shows simultaneously: (i) steady-state character with self-sharpening properties in a certain part of the boundary, demarcated by a certain range of its composition; (ii) unsteady-state character with EMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…pH is usually increasing toward the anode in anionic profiles. Recently, we have described various cases of nonlinearity in EMD profiles [14][15][16][17][18] and shown that in special cases EMD profiles may have the course of pH along the profile inverted [18]. The aim of this article is to show that this special type of EMD profile of inverse character is really capable of focusing nonamphoteric analytes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…pH is usually increasing toward the anode in anionic profiles. Recently, we have described various cases of nonlinearity in EMD profiles [14][15][16][17][18] and shown that in special cases EMD profiles may have the course of pH along the profile inverted [18]. The aim of this article is to show that this special type of EMD profile of inverse character is really capable of focusing nonamphoteric analytes.…”
Section: Introductionmentioning
confidence: 93%
“…EMD profiles have some special properties that are described in detail elsewhere [13,14]. Here, we briefly describe the characteristics of an anionic EMD profile potentially suitable for focusing.…”
Section: Theoreticalmentioning
confidence: 99%
“…progressively broadening) electrophoretic boundaries that are produced between strong and weak electrolytes upon current flow [2,3,46,64,126,127,139] (for examples see Figs. 4-6 and 8-12), was used to discover and understand new types of migrating boundaries [140][141][142][143], provided insight into the regulation principles associated with current flow [2,3,46,123,124,127,144] , which is a strong acid with a mobility equal to that of the buffer additive and which was sampled together with the neutral analytes. S and I refer to the anionically migrating system peak and the location of the initial sample compartment, respectively.…”
Section: Electrophoretic Boundaries and Regulation Principlesmentioning
confidence: 99%
“…The goal of FFZE is to achieve high resolution, which is reached by analytes migrating and electromigration dispersion (σ EMD ) [17,32]. Not all sources of band broadening are discussed here and the reader is referred to the literature for more details.…”
Section: Ffzementioning
confidence: 99%
“…Zones of different electrical conductivity in sample and carrier electrolyte will lead to electromigration dispersion [17,32]. This type of distortion results from different migration velocities of the analytes in zones having different electrical field strengths.…”
Section: Ffzementioning
confidence: 99%